(untitled) (Aporte Santiaguino, 2025)
The main objective was to analyze vorticity as a hydraulic phenomenon that influences fluvial scour around hydraulic structures. The methodology consisted of a review of bibliographies and scientific articles related to vorticity and its effect on scour. One of the relevant conclusions is that the deduction of the vorticity equation is carried out from the Navier – Stokes equation, which contains the advection terms and the rate of change of local vorticity in the first member; while the second member contains the vorticity stretching and diffusion terms. Vorticity advection consists of the transport of vorticity along the river, which contributes to general scour but more to local scour, vorticity stretching represents the intensification of vorticity in the direction of flow velocity, which contributes to local scour and vorticity diffusion which expresses vorticity attenuation. Wake vortex shedding is generated behind bridge piers and is evaluated using the Strouhal number.